A novel Li2CaSi2N4:Eu2+ orange‐red phosphor for field‐emission displays. Issue 6 (27th November 2018) - Wu, Quansheng; He, Ziyu; Zhang, Hanqiang; Chen, Hande; Zhou, Jiangcong; Xiong, Jinhua; Hu, Zhibiao
Abstract: The exploration of suitable phosphors with high efficiency, low saturation, and good stability has always been a key issue for field‐emission displays (FEDs) development. In this work, a novel Li2 CaSi2 N4 :Eu 2+ orange‐red phosphors were prepared by solid reaction process and the cathodoluminescence (CL) properties were investigated in detail to explore the potential application for FEDs. Under a low voltage electron‐beam excitation, the phosphors show an intense orange‐yellow emission in the range of 500‐700 nm, which belongs to the 4f 6 5d→4f 7 electron transition of Eu 2+ ion. The influences of the Eu 2+ doping concentration, filament current, accelerating voltage, and bombardment time on the CL emission of Li2 CaSi2 N4 :Eu 2+ were investigated in detail. The results indicate that Li2 CaSi2 N4 :Eu 2+ phosphors exhibit an intense orange‐red emission, no saturation effect, and excellent degradation property, which give the Li2 CaSi2 N4 :Eu 2+ phosphors potential application in full color FEDs.